Adaptation and Validation of the Brief Ryff's Psychological Well-Being Scale (Indonesian Version) for Honorary Teachers - Nurisma Sari; Nadia Salsabila Lutfha; Syarifah History Noversya; Yogi Surani; Hijriyati Cucuani (IJIP : Indonesian Journal of Islamic Psychology, 2026)
This study aims to adapt and validate the psychological well-being scale. The adaptation process involved translation, synthesis, and backward translation by Beaton et al. (2000). This instrument refers to the Psychological Well-Being Scale by Ryff (1989). The test of item distinctiveness using Corrected Item-Total Correlation analysis showed most items had significant correlations (p < 0.25), reflecting the instrument's ability to measure the relevant constructs. The reliability test yielded a Cronbach's Alpha value of 0.703, indicating adequate internal consistency. These results indicate that the instruments are valid and reliable for use in further research. The findings also provide insight into the importance of the psychological well-being of honorary teachers who face challenges such as low salaries and high workloads. The instrument is expected to help explore the factors that influence various matters related to honorary teachers' psychological well-being.